Evaluating the Impact of New Technologies on Quality of Healthcare services in Saudi Arabia: A Systematic Review - Alghamdi, Abdullah Safar; Nishaily, Ali Ibrahim; Kinani, Hanan Mohammed Gassim; Almahmood, Feras Mohammed; Alasiri, Fahad Ali; Hakami, Ahmed Taher; Al Harthi, Manal Abdulmohsen; Alsaedi, Jawaher Ahmed; Alarifi, Saud Mohammed; Kuriri, Majed Abdullah Hassan (Journal of Ecohumanism, 2024)
State-of-the-art healthcare technology including artificial intelligence, telemedicine, EHR systems, and blockchain systems now improves international health services delivery. Saudi Arabia uses these technologies to support its Vision 2030 goal of delivering superior quality care to more patients at reduced costs. Research finds the effectiveness of these healthcare solutions in Saudi Arabia lacks thorough evaluation on how projects face hurdles and bring lasting changes to healthcare service delivery.Aim: This systematic review aims to evaluate the impact of emerging healthcare technologies on the quality of healthcare services in Saudi Arabia, with a focus on AI, telemedicine, EHRs, and blockchain technologies. Method: The research employed PubMed, Scopus, IEEE Xplore, ScienceDirect, and Google Scholar electronic databases to retrieve studies from 2020 to 2024. The research selected appropriate studies according to the research question while the data extraction followed PRISMA guidelines. Results: The analysis of 10 high-quality studies established substantial healthcare quality and operational efficiency along with accessible healthcare because of AI combined with telemedicine and EHRs and blockchain implementations. Researchers discovered four main benefits that result from AI and blockchain adoption which include improved diagnostics as well as wider healthcare access coupled with better information protection and enhanced operational functions. The implementation of healthcare technologies faced barriers because healthcare workers struggled with digital skills as well as concerns about data privacy and increased cybersecurity exposure.Conclusion: Future healthcare technologies present the potential to transform Saudi Arabian healthcare delivery systems into higher quality services. The successful deployment of these technologies in the future demands resolution of security concerns along with raising digital abilities and delivering proper training for the workforce.